Prospective Study of Sleeve Gastrectomy in Baghdad Teaching Hospital - Salman, Hamid D.; Ahmed, Ahmed S.; Alzubaidi, Haider (Journal of the Faculty of Medicine Baghdad, 2014)
Fac Med Baghdad 2014; Vol.56, No.2 Received: April. 2014 Accepted May. 2014 Background: obesity is a common disease affecting more than 300 million adults worldwide. Laparoscopic sleeve gastrectomy (LSG) is a relatively new and effective procedure for weight loss, it is gaining acceptance among bariatric surgeons as a viable option for treating morbidly obese patients. We describe results of our experience with LSG in a community practice. Objective: We aimed to evaluate our experience with LSG with regard to its safety and feasibility and early weight loss. Methods: prospective study done in Baghdad Teaching Hospital between February 2011 and November 2013, of 50 consecutive morbidly obese patients and was designed to study the efficacy and safety of the sleeve gastrectomy in this group of patients. Results: The mean preoperative weight of the patients was 113.4 (range 91.0–170.0) kg, while the mean BMI was 42.6 (range 33.0– 60.0) kg/m2. Hypertension was present in 34%; hyperlipidaemia in 32% and Diabetes mellitus in 8% of the patients. The majority of patients had two or more obesity-related comorbidities (52 %). Mean operative time was 142 minutes and duration of postoperative stay was three to nine days. At two weeks, one, three and six months post operation, the mean BMI was 38.6 kg/m2, 37.8 kg/m2, 34.5 kg/m2 and 30.8 kg/m2, the mean percentage of excess weight loss was 17.7 %, 23.3 %, 40.9 % and 56.7 %, and absolute weight loss was 8.00 kg, 11.52 kg, 18.77 kg and 26.85 kg, respectively. Conclusion: LSG is a promising procedure for surgical treatment of obesity, with good early weight loss and low morbidity.